Cholinergic interactions between donepezil and prucalopride in human colon: potential to treat severe intestinal dysmotility. (28th October 2013) - Broad, J; Kung, V W S; Boundouki, G; Aziz, Q; De Maeyer, J H; Knowles, C H; Sanger, G J
Abstract : Background and Purpose: Cholinesterase inhibitors such as neostigmine are used for acute colonic pseudo‐obstruction, but cardio‐bronchial side‐effects limit use. To minimize side‐effects, lower doses could be combined with a 5‐HT4 receptor agonist, which also facilitates intestinal cholinergic activity. However, safety concerns, especially in the elderly, require drugs with good selectivity of action. These include the AChE inhibitor donepezil (used for Alzheimer's disease, with reduced cardio‐bronchial liability) and prucalopride, the first selective, clinically available 5‐HT4 receptor agonist. This study examined their individual and potential synergistic activities in human colon. Experimental Approach: Neuronally mediated muscle contractions and relaxations of human colon were evoked by electrical field stimulation (EFS) and defined phenotypically as cholinergic, nitrergic or tachykinergic using pharmacological tools; the effects of drugs were determined as changes in 'area under the curve'. Key Results: Prucalopride increased cholinergically mediated contractions (EC50 855 nM; 33% maximum increase), consistent with its ability to stimulate intestinal motility; donepezil (477%) and neostigmine (2326%) had greater efficacy. Concentrations of donepezil (30–100 nM) found in venous plasma after therapeutic doses had minimal ability to enhance cholinergic activity. However, donepezil (30 nM) together with prucalopride (3, 10 μM) markedly increased EFS‐evoked contractions compared with prucalopride alone ( P = 0.04). For example, the increases observed with donepezil and prucalopride 10 μM together or alone were, respectively, 105 ± 35%, 4 ± 6% and 35 ± 21% ( n = 3–7, each concentration). Conclusions and Implications: Potential synergy between prucalopride and donepezil activity calls for exploration of this combination as a safer, more effective treatment of colonic pseudo‐obstruction.